Adaptation of the Alphaproteobacterium Rhodobacter sphaeroides to stationary phase. (17th October 2019) - McIntosh, Matthew; Eisenhardt, Katrin; Remes, Bernhard; Konzer, Anne; Klug, Gabriele
Summary: Exhaustion of nutritional resources stimulates bacterial populations to adapt their growth behaviour. General mechanisms are known to facilitate this adaptation by sensing the environmental change and coordinating gene expression. However, the existence of such mechanisms among the Alphaproteobacteria remains unclear. This study focusses on global changes in transcript levels during growth under carbon‐limiting conditions in a model Alphaproteobacterium, Rhodobacter sphaeroides, a metabolically diverse organism capable of multiple modes of growth including aerobic and anaerobic respiration, anaerobic anoxygenic photosynthesis and fermentation. We identified genes that showed changed transcript levels independently of oxygen levels during the adaptation to stationary phase. We selected a subset of these genes and subjected them to mutational analysis, including genes predicted to be involved in manganese uptake, polyhydroxybutyrate production and quorum sensing and an alternative sigma factor. Although these genes have not been previously associated with the adaptation to stationary phase, we found that all were important to varying degrees. We conclude that while R . sphaeroides appears to lack a rpoS ‐like master regulator of stationary phase adaptation, this adaptation is nonetheless enabled through the impact of multiple genes, each responding to environmental conditions and contributing to the adaptation to stationary phase.